2021
DOI: 10.1177/1934578x211041421
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Composition and Anti-Rheumatoid Arthritis Mechanism of Qintengtongbi Decoction Based on Network Pharmacology

Abstract: Qintengtongbi Decoction (QTTBD) is a traditional prescription for rheumatoid arthritis (RA) treatment in Ruikang Hospital Affiliated to Guangxi University of Chinese Medicine, Nanning, southern China's Guangxi Zhuang Autonomous Region. However, there is not yet any analysis on its active compounds or action mechanism for treating RA. Moreover, the prescription has not been investigated from the perspective of network pharmacology. Therefore, this study aimed to analyze the compounds QTTBD and their potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…And the whole formula of QTTBD has the functions of dispelling wind and dampness, dispelling cold and eliminating paralysis, dredging collaterals and relieving pain, and can effectively prevent and treat RA. 9 The results of this recent study showed that compared with the model group, the proliferation of FLS cells in the QTTBD drug-containing serum treatment group was effectively inhibited (p <0 .01), and its apoptosis rate increased significantly (p <0 .05), which was positively correlated with the drug dosage and intervention time; the levels of IL-6, IL-1β, and TNF-α after QTTBD drug-containing serum intervention decreased significantly (p <0 .05), the expression of PI3K, AKT1, p-AKT1, and Bax protein was also lower than that in the model group (p <0 .05), while the expression of Bcl-2 increased (p < 0.05) To sum up, we could conclude that QTTBD could effectively inhibit the level of inflammatory factors of RA, effectively regulate the expression of related proteins, and relieve RA symptoms. However, there are still some problems that require researchers to make breakthroughs in future studies, including the small sample size of clinical case studies of drug treatment RA, role targets related to drug treatment, in-depth research on the mechanism of drug action, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And the whole formula of QTTBD has the functions of dispelling wind and dampness, dispelling cold and eliminating paralysis, dredging collaterals and relieving pain, and can effectively prevent and treat RA. 9 The results of this recent study showed that compared with the model group, the proliferation of FLS cells in the QTTBD drug-containing serum treatment group was effectively inhibited (p <0 .01), and its apoptosis rate increased significantly (p <0 .05), which was positively correlated with the drug dosage and intervention time; the levels of IL-6, IL-1β, and TNF-α after QTTBD drug-containing serum intervention decreased significantly (p <0 .05), the expression of PI3K, AKT1, p-AKT1, and Bax protein was also lower than that in the model group (p <0 .05), while the expression of Bcl-2 increased (p < 0.05) To sum up, we could conclude that QTTBD could effectively inhibit the level of inflammatory factors of RA, effectively regulate the expression of related proteins, and relieve RA symptoms. However, there are still some problems that require researchers to make breakthroughs in future studies, including the small sample size of clinical case studies of drug treatment RA, role targets related to drug treatment, in-depth research on the mechanism of drug action, etc.…”
Section: Discussionmentioning
confidence: 99%
“…And the whole formula of QTTBD has the functions of dispelling wind and dampness, dispelling cold and eliminating paralysis, dredging collaterals and relieving pain, and can effectively prevent and treat RA. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation